Hubungan keterampilan guru mengelola kelas dengan kemampuan berpikir kritis peserta didik pada pembelajaran ipas kelas iv sekolah dasar - Astuti, Utari Fitriyani; Marmoah, Sri Marmoah; Budiharto, Tri Budiharto (Didaktika Dwija Indria, 2025)
The primary objective of this research is to analyze the relationship of teacher’s classroom management skills with students' critical thinking ability in social and science learning for the fourth grade students at the state Elementary School of Ngebung Beran. The sample for this study consists of all students from fourth grade students at the State Elementary School of Ngebung Beran. The sampling technique applied is simple random sampling. Data were collected through questionnaires and tests. Internal validity in this study is assessed using content validity and construct validity, while the reliability of the instruments is measured using Cronbach's Alpha. The data analysis techniques applied include descriptive data analysis, prerequisite testing with normality and linearity tests, and hypothesis testing using product moment/Pearson correlation. The correlation coefficient between classroom management skills (X) and critical thinking ability (Y) is 0.955. The significance test results show that the calculated correlation coefficient (0.955) is greater than the table value (0.339) at the 5% significance level, with a sample size (N) of 36, indicating that the alternative hypothesis (Ha) is accepted. The implication of this study is that teachers can apply classroom management skills in social and science learning for fourth grade. Teachers who manage the classroom effectively, including managing time, building good relationships with students, and creating a supportive learning environment, will positively impact their ability to guide students in developing their critical thinking skills.